The impact of porosity on the formation of manganese based copper diffusion barrier layers on low-κ dielectric materials. (13th July 2015) - McCoy, A P; Bogan, J; Walsh, L; Byrne, C; O'Connor, R; Woicik, J C; Hughes, G
Abstract: This work investigates the impact of porosity in low- κ dielectric materials on the chemical and structural properties of deposited Mn thin films for copper diffusion barrier layer applications. X-ray photoelectron spectrscopy (XPS) results highlight the difficulty in distinguishing between the various Mn oxidation states which form at the interlayer dielectric (ILD)/Mn interface. The presence of MnSiO3 and MnO were identified using x-ray absorption spectroscopy (XAS) measurements on both porous and non-porous dielectric materials with evidence of Mn2 O3 and Mn3 O4 in the deposited film on the latter surface. It is shown that a higher proportion of deposited Mn converts to Mn silicate on an ILD film which has 50% porosity compared with the same dielectric material with no porosity, which is attributed to an enhanced chemical interaction with the effective larger surface area of porous dielectric materials. Transmission electron microscopy (TEM) and energy-dispersive x-ray spectroscopy (EDX) data shows that the Mn overlayer remains predominately surface localised on both porous and non-porous materials.